Peran Inkubator Bisnis dan Teknologi (IBT) Universitas Jambi dalam Pengelolaan Keuangan pada Bisnis Rintisan Gubuk Nenas Jambi (Studi Kasus pada Bisnis Rintisan Gubuk Nenas Jambi) - Dwi Istiqomah; Netty Herawaty; Reni Yustien (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2022)
This research aims to determine the role of Jambi University Business and Technology Incubator (IBT) in financial management process at Gubuk Nenas Jambi. This research also aims to determine the financial management process in Gubuk Nenas Jambi. This research is a qualitative descriptive research which shows the role of Jambi University’s IBT in conducting training and assistance in the financial management process at Gubuk Nenas Jambi. This research uses data collection techniques such as interview, literature study, and documentation of Gubuk Nenas Jambi’s financial records. The sampling technique carried out in this research used a purposive sampling technique. Data analysis carried out in the form of data collection, data reduction, data presentation, and drawing conclusions.